A Novel Ordinal Endpoint is Proposed to Evaluate Clinical Status Over Time in Hospitalized Patients with Influenza. (4th October 2017) - Butler, Lesley; Mathew, Nitya; Chia, Yifeng; Newton, Elizabeth; Kulkarni, Priya; Randhawa, Jessie; Clinch, Barry; Tavel, Jorge
Abstract: Background: Hospitalized patients with influenza are heterogeneous with respect to disease severity. A summary endpoint measure that can distinguish clinical improvement by disease severity is needed to effectively communicate the high unmet medical need in hospitalized patients with severe influenza. Methods: A retrospective cohort study was conducted using the U.S. Premier database. Patients discharged with an ICD– 9 or -10 code for influenza from January 1, 2008 to September 30, 2016 were included in this study. A score was assigned to each patient based on their status on each day of hospitalization as follows (value): death (6), Intensive Care Unit (ICU) with oxygen (ICU+O2 ) (5), ICU without oxygen (ICU-O2 ) (4), general ward with oxygen (Gen+O2 ) (3), general ward without oxygen (Gen-O2 )(2), discharged to other than home (1), and discharged to home (0). Admission status groups defined by ward type (ICU or Gen) and oxygen use (+O2 or -O2 ) were used to approximate disease severity on day 1. Results: Of the 183, 699 influenza patients, the Gen-O2 admission status group was the largest (67.4%), followed by Gen+O2 (27.2%), ICU-O2 (2.6%), and ICU+O2 (2.8%). Patient age (mea n = 53.1 years, SD 28.4) was similar across admission status groups, while having any respiratory comorbidity was more common among the ICU+O2 (52.4%) and Gen+O2 (52.7%) groups compared with the -O2 groups. In-patient mortality was highest among ICU+O2 patients (12.4%), followed by Gen+O2 (6.1%), ICU-O2 (4.0%), and Gen-O2 (1.7%). The median length of stay (LOS) was 4 days in all admission status groups, while the median ICU LOS was longer in the +O2 groups (4 days), compared with the -O2 groups (3 days). The Figure shows mean ordinal endpoint scores across days of hospitalization by admission status. The mean scores on day 7 were 2.6, 1.3, 1.2, and 0.6, for ICU+O2, ICU-O2, Gen+O2, and Gen-O2, respectively. All pairwise p values on day 7 were <0.001. On day 14, all pairwise p values were <0.001 except for ICU-O2 vs. Gen-O2 (p value = 0.7). Conclusion: Real world data was used to demonstrate the use of a novel ordinal endpoint summary score to communicate clinical status improvement in hospitalized patients with influenza. Future research is needed to assess the utility of the ordinal endpoint score in other populations. Disclosures: L. Butler, Genentech, Inc.: Employee, Salary; N. Mathew, Genen: Research Contractor, Salary; Y. Chia, Genentech, Inc.: Employee, Salary; E. Newton, Genentech, Inc.: Employee, Salary; P. Kulkarni, Genentech, Inc.: Employee, Salary; J. Randhawa, Roche: Employee, Salary; B. Clinch, Roche: Employee, Salary; J. Tavel, Genentech, Inc.: Employee, Salary